Dziedziczenie testamentowe rozwiedzionego małżonka - Dyoniak, Andrzej (Wydział Prawa i Administracji UAM, 1988)
The Civil Code provisions on succession by will, unlike the regulation of the intestate succession, do not give a definite answer as to whether a divorced spouse inherits after his/her ex-spouse by virtue of a testament drawn before the divorce. In some foreign legal systems the legislators not only stipulated the norms allowing the decedent to amend or cancell his/her will, but adopted the regulation according to which the very fact of divorce or even marital breakdown excludes the ex- -spouse from inheriting by virtue of a testament drawn prior to divorce. Trying to find a legal basis to exclude a divorced spouse from testamentary succession, one should point out to the provisions on error. Although at a time of drawing a will no defects can be found, the evaluation as to the existence of error in a testament must be carried out with reference to events which occured after the will had been drawn. Thus since in a typical case a decedent must consider divorce unexpected at a time of his/her drawing the will, subsequent divorce renders the stipulations Of a testament to have been drawn in error. A testament drawn in error is void. A court will have to assess whether the invalidity pertains to the entire testament or only to the stipulations in favour of the ex-spouse.
Testamentary succession by a divorced spouse